Аналіз ринку фріланса в Україні - Літорович, О. В.; Litorovych, O. (Видавництво Львівської політехніки, 2020)
Досліджено основні тенденції розвитку ринку фрілансерів в Україні та в світі. Зокрема охарактеризовано веб-ресурси фрілансерів: Freelancehunt, Freelance, Weblancer та Kabanchik. Визначено основні позиції замовлень на веб-ресурсах, такі як програмування, копірайтинг, дизайн та переклад текстів. Також проаналізовано ринок фрілансерів та виявлено постійне зростання чисельності фрілансерів як в Україні, так і у всьому світі, що має позитивні наслідки, оскільки в державі зменшується рівень безробіття. Однак серед проблем залишається недосконалість законодавчої бази, що призводить до відсутності реєстрації та в подальшому – до несплати податків.

The introduction of strict quarantine in many countries has raised the issue of workers' organization and the number of personnel needed. In this connection, the question of transferring some office workers to remote work or using freelancer`s labor has become actual. Accordingly, it is possible to predict the growth of demand at the freelance market and the change of the conjuncture of this market, which will significantly affect the activity of the domestic enterprises in the nearest future. The purpose of the article is to analyze the functioning of the main Internet platforms for purchase and sale of freelance services, their comparative analysis and definition of prospects for their development. The research also covers the review of the main world trends of freelance market development. In recent years, several powerful Internet sites for freelance job search have appeared in Ukraine. In particular, the article describes some web-resources for freelancers: Freelancehunt, Freelance, Weblancer, and Kabanchik. The main web-services for businesses in Ukraine are Kabanckik.ua, which is not a real freelance market in its classic sense, but more like a market for distant business with wide range of offers, and Weblancer.net, which is a classic internet platform for freelance businesses. During last several years the number of freelancers has been increasing exponentially, and the number of clients and projects has been increasing linearly. The most popular positions of the orders at the freelance market are programming, copywriting, design, and translation. The steady growth of number of freelancers has been identified both in Ukraine and around the world has a positive effect by decreasing the number of unemployed. However, the problems remain in the imperfection of the legislative base, which leads to the lack of registration and in the future – to the non-payment of taxes. The prospective are future studies of the impact of new technologies, in particular, artificial intelligence, virtual and augmented reality on the further development of the freelance market.
Analysis of the freelance market in Ukraine
Keywords: фріланс; фрілансер; проект; замовник; виконавець; freelance; freelancer; project; client; contractor; M; 54; О; 33; 331; 334